ANALISIS KEPRIBADIAN TOKOH UTAMA DALAM NOVEL YESUS (KISAH TENTANG PENCERAHAAN) KARYA DEEPAK CHOPRA - Lestari, Wiwin Dwi (BAHASANTODEA, 2016)
The objective of this research is to (1) describe the personage character and make a personage in the yesus novel written by Deepak Chopra. Kind of this research is qualitative descriptive. The data which used of this research is sentence, which it gets in the Yesus novel written by Deepak Chopra. The data accumulation of this reseacrh is done with refferences and note form technique. The instrument of this research is the researcher was direct to be a key instrument. While the data analysis technique is done with connecting the problem which it exists about the perconage character and make a personage, and the personality of main personage then will be analyzed using literature psychology investigate. The result of this research are (1) the personage character and make a character in the Yesus Novel is, Yesus, Yusuf, Maria (Yesus Mother’s) Yakobus, Simon, Yudas, Querulus, Mari Magdahlena, Tobias of Personage character, the main character is Yesus who has an honesty character, patient and always helps each other and also always loyal in the learning of religion, the other personage in the Yesus Novel are, Yusuf has a patient and wise character, Maria (Yesus Mother’s) is a woman who has a patient and merciful lord character, Yakobus has a kind character, Simon has a hard Character, Yudas has a hard character and he is a rebel person, Querulus has a helpful and patient character, Maria Magdahlena has merciful lord character and Tobias has a kind and wise character. Then (2) the personality influenced by Id, egoist and superegoist in the psychoanalysa of Simund Freud